Assessing the productivity of indigenous chickens in an extensive management system in southern Nyanza, Kenya - Olwande, P.O.; Ogara, W.O.; Okuthe, S.O.; Muchemi, G.; Okoth, S.; Odindo, M.O.; Adhiambo, R.F. (Springer, 2010)
The present study was conducted to assess the performance of indigenous chickens under extensive system in southern Nyanza, Kenya. The study was carried out in two phases in Komolorume and Kawere villages in Rongo and Rachuonyo districts, respectively. The first phase was a cross-sectional study in 81 farms selected by cluster sampling to get the overview of the indigenous chicken production. A four-month prospective longitudinal study in 60 farms randomly selected from the previous 81 farms followed. Mean flock sizes per household were 20 and 18 birds in Komolorume and Kawere, respectively. Overall mean flock size was 19 birds ranging from 1to 64. The mean clutch size, egg weight and hatchability were 12 eggs, 48 g and 81% respectively in Komolorume and 10 eggs, 45 g and 70%, respectively, in Kawere. The chick survival rates to the age of eight weeks were 13% and 10% in Komolorume and Kawere, respectively. Mean live weights for cocks and hens were 2096 g and 1599 g in Komolorume and 2071 g and 1482 g in Kawere, respectively. The mean household cock to hen ratio was 2:5 and 2:4 for Komolorume and Kawere, respectively. The mean chick to grower to adult ratio per household was 8: 6:6 in Komolorume and 8:4:6 in Kawere. Clutch sizes and hatchability rates were significantly higher in Komolorume village (P < 0.5). The productivity of the indigenous chickens was shown to be low compared to that of the improved chickens in other parts of the world.